Family Violence and Judicial Empathy: managing Personal Cross Examination in Australian Family Law Proceedings - Booth, Tracey (Oñati Socio-Legal Series, 2019)
Enquiries and research reveal that many victims of family violence who are personally cross-examined by the alleged perpetrator of that violence in family law proceedings find the process traumatising and intimidating. Not only can such processes generate unsafe and unfair outcomes but also they are unlikely to produce the high quality evidence required by the court. In deference to the emotional wellbeing and vulnerability of these victims, a number of measures for receiving such evidence are available to Australian Family Court judges. However, currently these are all discretionary powers and anecdotal evidence suggests that the use of these tools is unpredictable and dependent on the individual judge. In the absence of empirical evidence, this paper aims to open up potential emotional dimensions of judicial decision-making in this context with a view to exploring these theoretical ideas in later empirical work.